Couples coping with nutrition-related problems in advanced cancer: A qualitative study in primary care. (February 2019) - Opsomer, Sophie; Joossens, Sofie; De Wit, Claudia; Lauwerier, Emelien; Pype, Peter
Abstract: Purpose: Nutrition-related problems are common in patients with advanced cancer. They can disrupt daily life and routines. This study aimed to explore how couples cope with this source of distress. Methods: A qualitative descriptive study design was adopted using semi-structured interviews. Seven couples, each consisting of an advanced cancer patient and his or her co-habiting life partner, participated. The Qualitative Analysis Guide of Leuven (QUAGOL) was used as a guide to facilitate the analysis process. Results: When a patient communicates nutrition-related problems to the partner, individual coping is often complemented by interactive couple-coping pathways, serving two resilient coping strategies: maintaining normality and creating a new normality. These pathways can have either a practical, an emotional or a distant orientation. Different couple-coping pathways can be observed in the same couple when they are dealing with either one or multiple nutrition-related problems. Some couples, however, seem to cope more rigidly, often those with less observed 'we-ness'. Conclusions: Nutrition-related problems are inherent to advanced cancer and are perceived as health-threatening. Couple-coping with nutrition-related problems is a dynamic and interactive process leaning on different coping pathways. There is no evidence that one pathway is superior to another, as they all serve a resilient coping strategy. Our findings can assist homecare nurses and other professional caregivers in providing psychological support and advice to couples confronted with nutrition-related problems in advanced cancer. Future research should shed light on whether an unsuitable match in coping styles within a couple is one of the precursors of non-resilient outcomes. Highlights: Couple-coping with nutrition-related problems (NRP) leans on coping pathways with either a practical, emotional or distant orientation. Multiple couple-coping pathways can be observed in resilient couples. There is no pathway that is superior to another. We-ness seems to be associated with the use of a mix of different pathways, and to lead to a more resilient way of coping.